ISOLASI DAN KARAKTERISTIK BAKTERI LIMBAH LUMPUR MINYAK BUMI (OIL SLUDGE) DI AREA PT PERTAMINA KECAMATAN LIRIK SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK BIOLOGI SMA - Iasah, Bella; Sayuti, Irda; Natalina, Mariani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was conducted to determine the bacteria characteristicsof oil sludge waste in the area of PT Pertamina, Lirik district and its potential toproduce student worksheet designs with subject characteristics of bacteria in class XSMA KD 3.5 and 4.5. This research was conducted from December 2018 to March2019 at the Microbiology Laboratory, Faculty of Medicine, University of Riau. Thisstudy used two stages the first stage of research using qualitative descriptive todetermine the characteristics of bacteria in oil sludge waste. The parameters of thisstudy are characteristics of bacteria isolated from samples of oil sludge waste in LirikDistrict through macroscopic observations (colony shape, colony margin, colony color,and colony elevation), and microscopic (gram stain and cell shape). Phase II researchis the design of student worksheet teaching subject that uses two stages, those areanalysis and design stages. The results showed that the bacteria found had thecharacteristics of round, irregular, and filamentous. The elevations found are raised,flat, and umbonate. The margin of the colonies found were flat and lobate. The colors ofthe colonies found were white and yellow. The most common form of cells found wasrods, the most common gram found was gram negative. And the most common cell colorfound is purple. The results of this study can be used as a learning resource in the formof a student worksheet design for the subject characteristics of bacteria class of X inHigh School.Key Words : Isolation, Characteristics, Worksheets